Yaropolk Yevgenovych Yatskewich - Lviv National Medical University named Danilo Galician, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article is dedicated to the memory of Doctor of Medical Science, Professor Ya.Ye. Yatskewich: a scientist, pedagogue, doctor, Head of the Department of Traumatology, Orthopaedics and Field Surgery of Danylo Halytskyi Lviv National Medical University.